Surface curvature effects on the tonal noise performance of a low Reynolds number aerofoil. (October 2017) - Shen, Xiang; Avital, Eldad; Zhao, Qinghe; Gao, Junhui; Li, Xiaodong; Paul, Gordon; Korakianitis, Theodosios
Abstract: This paper presents wind tunnel experiments to illustrate the effects of surface curvature on the aeroacoustic performance of airfoil E387. For the first time, surface curvature effects are considered in an investigation of the airfoil's self-noise. To distinguish the effects of surface curvature, the CIRCLE method is applied to the airfoil E387 to remove slope-of-curvature discontinuities and the redesigned airfoil is denoted A7. Anechoic wind tunnel tests were performed with E387 and A7 at three low Reynolds numbers to investigate aeroacoustic performance by measuring airfoil self-noise at different angles of attack (AoA) and spatial positions. At 2° and 4° AoA, A7 presents a tone with a reduced amplitude compared with E387 due to its improved slope-of-curvature distribution. It is concluded that improving surface curvature distribution improves airfoil aeroacoustic performance.